Incidence of muscle wasting in the critically ill: a prospective observational cohort study - Hrdy, Ondrej; Vrbica, Kamil; Kovar, Marek; Korbicka, Tomas; Stepanova, Radka; Gal, Roman (Scientific reports, 2023)
Loss of muscle mass occurs rapidly during critical illness and negatively affects quality of life. The incidence of clinically significant muscle wasting in critically ill patients is unclear. This study aimed to assess the incidence of and identify predictors for clinically significant loss of muscle mass in this patient population. This was a single-center observational study. We used ultrasound to determine the rectus femoris cross-sectional area (RFcsa) on the first and seventh day of ICU stay. The primary outcome was the incidence of significant muscle wasting. We used a logistic regression model to determine significant predictors for muscle wasting. Ultrasound measurements were completed in 104 patients. Sixty-two of these patients (59.6%) showed ≥ 10% decreases in RFcsa. We did not identify any predictor for significant muscle wasting, however, age was of borderline significance (p = 0.0528). The 28-day mortality rate was higher in patients with significant wasting, but this difference was not statistically significant (30.6% versus 16.7%; p = 0.165). Clinically significant muscle wasting was frequent in our cohort of patients. Patient age was identified as a predictor of borderline significance for muscle wasting. The results could be used to plan future studies on this topic.Trial registration: ClinicalTrials.gov NCT03865095, date of registration: 06/03/2019.
Keywords: kvalita života; Prospective Studies; Quadriceps Muscle; svalová atrofie; Intensive Care Units; čtyřhlavý sval stehenní; Incidence; Muscular Atrophy; kritický stav; ultrasonografie; Humans; lidé; incidence; jednotky intenzivní péče; Quality of Life; Critical Illness; Ultrasonography; prospektivní studie